Guiding Principles for Surgical Pathways: A Tool for Improving Outcomes and Patient Safety - Bolcato, Matteo; Rodriguez, Daniele; Aprile, Anna (Frontiers in Public Health, 2022)
Surgical activity is an important aspect for the management of health and safety processes and from an organizational perspective is one of the most complex activities performed in hospitals. It is often a defining and high value feature for any healthcare facility while being one of the most high-risk procedures for patients with the highest number of avoidable adverse events. To ensure effective management of surgical pathways, they need to be considered from the perspective of clinical governance which takes a global approach to planning and management with the goal of improving safety and quality for patients. This paper contains the main features of this objective outlined within the document issued subsequent to the State-Regional Italian Government conference. This regulatory effort includes effective recommendations to make surgical pathways safer and more efficient with particular reference to lean management, patient blood management and patient safety.